Probability – Proving Renyi’s Result on Order Statistics of Exponential Distribution

beta functionexponential distributionprobability

The Wikipedia article on order statistics mentions the following result on the order statistics of an exponential distribution with rate parameter, $\lambda$:

$$X_{(i)} = \frac{1}{\lambda}\sum\limits_{j=1}^i \frac{Z_j}{n-j+1} \tag{1}$$

It provides no proof of this. How do I prove it?


My attempt:

We know that to get X_{(i)} for a distribution with inverse CDF $F_X^{-1}(x)$, we first get the corresponding order statistic of the uniform ($U_{(i)}$) and then apply the inverse CDF to it.

We know that $U_{(i)} \sim B(i,n-i+1)$. And the inverse CDF of the exponential distribution is: $F_X^{-1}(x) = -\frac{\log(1-x)}{\lambda}$.

This means that the distribution of $X_{(i)}$ should be: $-\frac{\log(1-U_{(i)})}{\lambda}$

Also, $1-U_{(i)} \sim U_{(n-i)}$. So, the distribution of the order statistic becomes:

$$X_{(i)}\sim -\frac{\log(U_{(n-i)})}{\lambda}$$

We have a Beta inside a logarithm. Don't see a path to equation (1) except maybe expressing the Beta as a Gamma and then noting that the Gamma is a sum of exponentials?

Best Answer

This can be shown quite directly. Fix an $i$. Then note that $$ P(X_{(i+1)} -X_{(i)}> x| X_{(i)} = y) = P(X_{(i+1)} > x+y|X_{(i) } = y).$$

Now, the latter probability is that of finding that the smallest of $n-k$ exponential random variables is bigger than $x+y$, given that each is at least $y$. But, due to the independence, and the memorylessness of the exponential distribution, this just works out to $n-i$ independent exponentials being bigger than $x$, i.e. $$ P(X_{(i+1)} - X_{(i)} > x| X_{(i)} = y) = e^{-\lambda (n-i) x}. $$ But, since the right hand side is independent of $y$, we can integrate over the conditioning and conclude that $X_{(i+1)} - X_{(i)}$ has the distribution of a $\mathrm{Exp}( \lambda (n-i))$ random variable. Further, this random variable is independent of $X_{(i)}$

In fact, yet more is true - instead of conditioning over only the value of $X_{(i)},$ we could have conditioned on the values of $X_{(0)} := 0, X_{(1)}-X_{(0)}, X_{(2)} - X_{(1)}$ and so on all the way to $X_{(i)} - X_{(i-1)}$ without changing the conclusion or the reasoning (again, this critically relies on the memorylessness of the exponential law). This means that

  1. $ \{ X_{(i+1)} - X_{(i)} \}_{i = 0}^{n-1} $ are mutually independent,
  2. $X_{(i+1)} - X_{(i)}$ is $\mathrm{Exp}(\lambda (n-i))$ distributed, which in turn is the same as the law of $Z/\lambda(n-i)$ for a standard exponential $Z$.

But now the result is obvious - \begin{align} X_{(i)} &= \sum_{j = 0}^{i-1} X_{(j+1)} - X_{(j)} \\ &\equiv \sum_{j = 0}^{i-1} \frac{Z_j}{\lambda (n - j)}.\end{align}

Related Question